2020
DOI: 10.17138/tgft(8)234-249
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of lactic acid bacteria associated with tropical grass silage produced in Okinawa

Abstract: In Okinawa, rate of increase in gross agricultural production during 2011‒2016 was the highest in Japan and sales of calves ranked fourth throughout Japan. Raising cattle by feeding high quality silage is beneficial both nutritionally and economically. However, little is known about lactic acid bacteria (LAB) present in silages made from tropical grass in Okinawa. To improve understanding of fermentation processes in silages, the LAB present in a range of silages (Digitaria eriantha, Megathyrsus maximus, Chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Stackebrandt and Goebel (2006) reported that a 16S rDNA sequence similarity range of above 98.7%–99% should be mandatory for testing the genomic uniqueness of novel isolates; species characterized by having lower than 98.7% of 16S rDNA sequence similarity with other type strains should be considered as new species, although there could be some exceptional cases. In Okinawa, which consists of many islands in the subtropical region, unique microflora may exist, and several kinds of microorganisms from this region have unique characteristics (Hanagasaki, 2020). Accordingly, it is quite likely that the isolates in this study are new species with unique characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Stackebrandt and Goebel (2006) reported that a 16S rDNA sequence similarity range of above 98.7%–99% should be mandatory for testing the genomic uniqueness of novel isolates; species characterized by having lower than 98.7% of 16S rDNA sequence similarity with other type strains should be considered as new species, although there could be some exceptional cases. In Okinawa, which consists of many islands in the subtropical region, unique microflora may exist, and several kinds of microorganisms from this region have unique characteristics (Hanagasaki, 2020). Accordingly, it is quite likely that the isolates in this study are new species with unique characteristics.…”
Section: Discussionmentioning
confidence: 99%